Accelerated Shelf Life Testing of Jackfruit Extract Powder - Loebis, Enny Hawani; Junaidi, Lukman (Biopropal Industri, 2013)
Jackfruit is a potential tropical fruit as raw material for food industry. Jackfruit could be processed by co-crystallization technique to extend its shelf life and increase its value. This research was conducted to study and to determine the shelf life of jackfruit powder extract. Shelf life test is conducted using variety of treatments such as: anti-caking types and temperature storage. The results showed that the shelf life of the jackfruit extract powder using anti-caking of magnesium oxide (MO), magnesium carbonate (MC), dan magnesium silicate (MS), which is store in the temperature of 27Â°C, were: 8.06, 5.42, and 5.5 months respectively. The variation of anti-caking type was significantly affect the product shelf life. Â The effect of storage temperature on the product shelf life is more significant for the product using anti-caking MO compared with product using anti-caking MC and MS.